Novel pH-responsive nanoparticles - Filippov, Sergey; Hrubý, Martin; Konák, Cestmír; Macková, Hana; Spírková, Milena; Stepánek, Petr (Langmuir, 2008)
In this work we report a new type of pH-responsive micelle-like nanoparticle. Reversible nanoscale structures are formed in solutions of a pH-sensitive hydrophobic polyelectrolyte, poly( N-methacryloyl- l-valine) or poly( N-methacryloyl- l-phenylalanine), and nonionic surfactant (Brij 98) in the presence of hydrochloric acid. The influence of composition and pH on particles size and shape was investigated by a variety of methods. An entity's size and polydispersity could be varied in a broad range making them a perspective candidate as a drug carrier. Unlike the case of typical micelles, our results indicate the presence of cavities in the formed particles. A hypothetical model of a nanoparticle and mechanism of formation are proposed.
Keywords: povrchové vlastnosti; elektrolyty; Plant Oils; micely; polyethylenglykoly; Scattering, Radiation; Models, Chemical; Nanoparticles; Valine; nanočástice; Hydrogen-Ion Concentration; fenylalanin; Phenylalanine; Microscopy, Atomic Force; Polymers; světlo; koncentrace vodíkových iontů; mikroskopie atomárních sil; Polyethylene Glycols; Micelles; polymery; valin; Nanotechnology; Surface Properties; radiační rozptyl; oleje rostlin; ionty; Light; Ions; chemické modely; nanotechnologie; Electrolytes